Progress in medicinal chemistry. - Witty, D. R. (David R.); Cox, Brian (Chemist) (Elsevier, 2017)
"Progress in Medicinal Chemistry, Volume 56 provides a review of eclectic developments in medicinal chemistry. This volume includes chapters covering recent advances in cancer therapeutics, fluorine in medicinal chemistry, a perspective on the next generation of antibacterial agents derived by manipulation of natural products, a potential new era for Chagas Disease drug discovery, and imaging in drug development. Specific chapters cover timely topics, such as the development of LRRK2 inhibitors for the treatment of Parkinson's, and recent discoveries and developments in TRPA1 modulators. Users will find a comprehensive resource on the topic of medicinal chemistry that also discusses avenues for the acceleration of drug discovery programs"--Publisher's description.